The Illegal Racing Community Phenomenon: A Case Study of the Meaning of Toxic Masculinity Behavior in Krian - Astutik, Murni Widi; Paryontri, Ramon Ananda (Psikostudia : Jurnal Psikologi, 2022)
Often illegal racing activities are considered as meaningless activities and cause negative impacts by the wider community, but this actually creates a positive side for the perpetrators. This study aims to see how toxic masculinity behaves and what are the benefits to the wild racing community. The method used is a qualitative research method with a case study approach, with analysis using coding techniques. The subject of this study used 4 participants, namely the four participants were perpetrators of illegal racing in the Krian area and supported by 4 participants as significant others. Based on the results of the analysis of the four participants, it shows that the behavior of toxic masculinity arises due to the masculine factors possessed by the perpetrators. Toxic masculinity behavior is indicated by the presence of self-esteem, self-actualization, and affiliation. Self-esteem is shown because participants feel they have courage and feel disapproving when they are insulted by others. Self-actualization is indicated by the emergence of potentials that arise when participants take part in wild racing. Affiliates appear with behavior that supports each other, becomes a support system, and motivates each other. These three behaviors arise because they are influenced by self, family, social and economic factors. Seringkali kegiatan balap liar dianggap sebagai kegiatan tidak bermakna dan menimbulkan dampak negatif oleh masyarakat luas, namun hal ini justru menimbukan sisi positif bagi para pelakunya. Penelitian ini bertujuan untuk melihat bagaimana perilaku toxic masculinity dan apa manfaat pada komunitas balap liar. Metode yang digunakan adalah metode penelitian kualitatif dengan pendekatan studi kasus, dengan analisis menggunakan teknik koding. Subjek penelitian ini menggunakan 4 partisipan, yaitu keempat partsipan tersebut adalah pelaku balap liar di wilayah krian dan didikung oleh 4 partisipan sebagai significant others. Berdasarkan hasil analisis keempat partisipan menunjukkan bahwa perilaku toxic masculinity muncul dikarenakan adanya faktor maskulin yang dimiliki oleh para pelaku. Perilaku toxic masculinity ditunjukkan dengan adanya self-esteem, aktualisasi diri, dan afiliasi. Harga diri dutunjukkan karena partisipan merasa memiliki keberanian dan merasa tidak terima ketika dirinya dihina oleh orang lain. Aktualisasi diri ditunjukkan dengan munculnya potensi-potensi yang muncul ketika partisipan mengikuti balap liar. Afiliasi muncul dengan perilaku yang saling mendukung, menjadi support system, dan saling memotivasi antara satu dengan yang lainnya. Ketiga perilaku tersebut muncul karena dipengaruhi oleh faktor diri sendiri, keluarga, lingkungan sosial, serta ekonomi.